2016
DOI: 10.1002/art.39665
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin‐Dependent Kinase IV Facilitates the Recruitment of Interleukin‐17–Producing Cells to Target Organs Through the CCR6/CCL20 Axis in Th17 Cell–Driven Inflammatory Diseases

Abstract: Objective The recruitment of IL-17-producing T helper (Th17) cells to inflammatory sites has been implicated in the development of organ damage in inflammatory and autoimmune diseases including systemic lupus erythematosus (SLE). To define the mechanism of CaMK4 activation on Th17-cell recruitment to target tissues, we performed anti-glomerular basement membrane antibody-induced glomerulonephritis (AIGN) experiments in mice and studied samples from patients with SLE. Methods We induced experimental AIGN in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…It has been shown previously that expression of CCR6 on T effector cells positively correlates with the severity of organ impairment in SLE patients 33 , and CCR6/CCL20 axis aids in recruitment of IL-17 producing cells into targeted tissue, and, thus, results in tissue injury 24 , 33 . To validate these findings and have further clarify the mechanism of CCR6 + Th cells in the SLE organ impairment, we stratified SLE patients in our study into different subgroups (SK, SS, KS and NSK) based on skin and renal impairment.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown previously that expression of CCR6 on T effector cells positively correlates with the severity of organ impairment in SLE patients 33 , and CCR6/CCL20 axis aids in recruitment of IL-17 producing cells into targeted tissue, and, thus, results in tissue injury 24 , 33 . To validate these findings and have further clarify the mechanism of CCR6 + Th cells in the SLE organ impairment, we stratified SLE patients in our study into different subgroups (SK, SS, KS and NSK) based on skin and renal impairment.…”
Section: Discussionmentioning
confidence: 95%
“…A significant association between CCR6 gene polymorphism and susceptibility to LN in SLE patients has also been reported ( Zhou et al, 2015 ). Furthermore, it has been identified that CCR6 chemokine expressed by the effector/memory CD4 + T cells plays a role tissue damage in SLE patients, including LN or neuropsychiatric SLE patients, and probably functions through CCR6/CCL20 axis at the inflamed sites ( Koga et al, 2016 ). These observations tentatively indicate that CCR6 + Th cells might be engaged in the aggravation of inflammatory reactions, and thus contributes to worse disease outcomes in anti-DNA + SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokines expressed by T cells, including TNF- α and IL-17, both of which play an active role in autoimmunity, are increased in SLE patients ( Vincent et al, 2013 ). Moreover, the chemokine receptor, CCR6, expressed on Th cells, has been implicated in mediating the recruitment of IL-17 producing cells in glomerulonephritis ( Koga et al, 2016 ; Turner et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a murine model, blockade of T H 17 cell differentiation led to an amelioration of experimentally induced nephritis and reduction of infiltrating T H 17 cells. 57 Correspondingly, there was a decrease in Il17a, Ccr6 and Ccl20 mRNA expression in the kidneys of these mice relative to control mice. 57 Similarly, Yang et al 58 demonstrated that when a T H 17 cell-inhibiting compound derived from a herb (Baicalin) was administered to lupus-prone mice, the mice had a marked reduction in glomerulonephritis as assessed by histology and urine protein.…”
Section: Follicular Helper T Cells and Subsetsmentioning
confidence: 81%
“…57 Correspondingly, there was a decrease in Il17a, Ccr6 and Ccl20 mRNA expression in the kidneys of these mice relative to control mice. 57 Similarly, Yang et al 58 demonstrated that when a T H 17 cell-inhibiting compound derived from a herb (Baicalin) was administered to lupus-prone mice, the mice had a marked reduction in glomerulonephritis as assessed by histology and urine protein. The treated mice also had a reduction in infiltrating T H 17 cells and a corresponding reduction in Ccl20 in kidneys compared with vehicle control-administered mice.…”
Section: Follicular Helper T Cells and Subsetsmentioning
confidence: 81%